Patterns of postnatal weight gain and its predictors among preterm very low birth weight neonates born in Bahir-Dar city public hospitals, 2022: A cross sectional study - Yihenew Ayehu Dessie; Worku Abemie; Elda Mekonnen Nigussie; Bethelehem Taye Mengistu; Leweyehu Alemaw Mengstie; Bekahegn Girma; Solomon Hailemeskel (PLoS ONE, 2025)
Introduction Postnatal weight gain in very low birth weight infants remains a challenge during the neonatal period in low and middle-income countries like Ethiopia, where no feeding alternatives and follow-up charts are available. Although extrauterine growth retardation is a common problem in preterm very low birth weight infants, there is a lack of evidence in resource-limited countries regarding patterns of postnatal weight gain. Therefore, this study aimed to assess the patterns of postnatal weight gain and its predictors among preterm very low birth weight infants in Ethiopia. Methods A cross-sectional study was conducted on a randomly selected sample of 412 neonates in Ethiopia. Data were collected using structured questionnaires and analyzed with Stata version 14.0 software. Bivariable and multivariable logistic regression analyses were performed to identify significant predictors. Model fitness and assumptions were assessed. Associations were reported using adjusted odds ratios (AOR) with 95% confidence intervals. Results In the current study, 14.6% (95% CI: 10.4–20.1) of neonates had adequate postnatal weight gain at discharge. Spontaneous vaginal delivery [AOR: 2.54; 95% CI (1.17, 5.54)], birth Z-score > -1.29 [AOR: 4.51; 95% CI (1.43, 14.16)], early feeding initiation time [AOR: 3.36; 95% CI (1.63, 6.92)], and respiratory distress syndrome [AOR: 0.31; 95% CI (0.12, 0.78)] were significant predictors for postnatal weight gain among very low birth weight neonates in Ethiopia. Conclusion The postnatal weight gain reported in this study was low as compared to the national figure. Mode of delivery, birth z-score, initiation time of the first feeding, and respiratory distress syndrome were associated with postnatal weight gain. The Federal Ministry of Health, stakeholders, national neonatal associations, and non-governmental organizations should work collaboratively to promote vaginal delivery and early initiation of feeding and develop guidelines specifically tailored for this special population. Furthermore, healthcare providers should prioritize and focus on neonates who have respiratory distress and low Z-scores.